Wind regime and aeolian landforms on the eastern shore of Qinghai Lake, Northeastern Tibetan Plateau, China. (May 2021) - Hu, Guangyin; Dong, Zhibao; Zhang, Zhengcai; Yang, Linhai; Hao, Lewei; Hesp, Patrick; Miot da Silva, Graziela
Abstract: Wind regime is typically highly variable in space and in time, and the studies of aeolian geomorphology often use a single meteorological station as representative of a specific dune field due to the scarcity of meteorological stations in remote areas. However, the wind regime may vary greatly even between sites located just a few kilometers apart. In this study, to fully understand the relationship between wind regime and aeolian landforms of the dune field on the eastern shore of the Qinghai Lake, 1-year hourly recorded wind data from an average wind year 2012 from four stations, namely Gangcha Station, Eri Station, Wendu Station and Daotanghe Station was used to analyze the wind regime and resultant potential sand transport. The wind data analysis revealed that the drift potential (DP) at Gangcha, Eri, Wendu and Daotanghe stations is 144, 537, 829 and 431 VU, respectively. The resultant drift potential (RDP) at Gangcha, Eri, Wendu and Daotanghe stations is 112, 143, 544 and 125 VU, respectively. The high-energy wind environment, in addition to multidirectional and locally highly variable wind regime are the principal factors likely responsible for the coexistence of several types of aeolian landforms (e.g., Reversing transverse, barchanoid and stardunes). Highlights: Hourly recorded wind data from four stations was used for wind regime analysis. Wind regime is highly variable in space on the eastern shore of Qinghai Lake. High-energy, multidirectional and locally variable wind are responsible for the coexistence of types of aeolian landforms.